BIOTIC COMMUNITIES OF A KUMAON HIMALAYAN RIVER - THE GAULA 2. PLANKTON - SUNDER, SHYAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Quantitative studies from the various sections of Kumaon himalayan river Gaula revealed the abundance of phytoplankton (>97%) amongst the total plankton assemblages. Phytoplankton mainly comprised of Bacillariophyceae (85.3 -96.0%), Chlorophyceae (3.60 - 10.66%), Cyanophyceae (0.0 - 4.62%) and Dinophyceae (0.0 - 3.03%). In all 46 genera of phytoplankton and 16 of zooplankton were recorded. Seasonal abundance and distribution of various plankters in the system are highlighted.